Forbidden love a harrowing true story of love and revenge in Jordan - Khouri, Norma; Khouri, Norma (New York Bantam Books, 2003)
Dalia was a young, beautiful, Arabian Muslim living with her family in Amman, Jordan. This text gives a harrowing account by a Jordanian woman of the honour-killing of her lifelong friend at the hands of her own father, after she fell in love with a young Catholic man.
American ed. published under title: Honor lost.
Keywords: Filicide -- Jordan -- Case studies; Women -- Crimes against -- Jordan; Women -- Legal status, laws, etc. -- Jordan; Women -- Crimes against -- Religious aspects -- Islam; Murder -- Jordan -- Religious aspects